The association of sex with outcomes among patients undergoing primary percutaneous coronary intervention for ST elevation myocardial infarction in the contemporary era: Insights from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium (BMC2) - Jackson, Elizabeth A.; Moscucci, Mauro; Smith, Dean E.; Share, David; Dixon, Simon; Greenbaum, Adam; Grossman, Paul M.; Gurm, Hitinder S. (The American heart journal, 2011)
Historically, women with ST elevation myocardial infarction (STEMI) have had a higher mortality compared with men. It is unclear if these differences persist among patients undergoing contemporary primary percutaneous coronary intervention (PCI) with focus on early reperfusion. We assessed the impact of sex on the outcome of 8,771 patients with acute STEMI who underwent primary PCI from 2003 to 2008 at 32 hospitals participating in the Blue Cross Blue Shield of Michigan Cardiovascular Consortium PCI registry. A propensity-matched analysis was performed to adjust for differences in baseline characteristics and comorbidities between men and women. Twenty-nine percent of the cohort was female. Compared with men, women were older and had more comorbidity. Female sex was associated with a higher unadjusted in-hospital mortality (6.02% vs 3.45%, odds ratio [OR] 1.79, 95% CI 1.45-2.22, P < .0001) and higher risk of contrast-induced nephropathy (OR 1.75, P < .0001), vascular complications (OR 2.13, P < .0001), and postprocedure transfusion (OR 2.84, P < .0001). The gap in sex-specific mortality narrowed over time. In a propensity-matched analysis, female sex was associated with a higher rate of transfusion (OR 1.88, 95% CI 1.57-2.24, P < .0001) and vascular complications (OR 1.65, 95% CI 1.26-2.14, P < .0002); but there was no difference in mortality (OR 1.30, 95% CI 0.98-1.72, P = .07). Women make up approximately one third of patients undergoing primary PCI for STEMI. Female sex is associated with an apparent hazard of increased mortality among patients undergoing primary PCI for STEMI, but this difference is likely explained by older age and worse baseline comorbidities among women.